1997
DOI: 10.1097/00007890-199712270-00012
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of Basiliximab, an Interleukin-2 Receptor Monoclonal Antibody, in Recipients of Mismatched Cadaver Renal Allografts1

Abstract: Total basiliximab doses of 40-60 mg were well tolerated, nonimmunogenic, and estimated to provide immunoprophylaxis to cover the first posttransplant month.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
62
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(70 citation statements)
references
References 5 publications
7
62
0
1
Order By: Relevance
“…The rate of CMV-reactivation in our patients was within the expected range after allogeneic SCT. 18 A causal relation between fatal systemic inflammatory response syndrome and basiliximab in one of our patients more than 3 months after use of the antibody seems to be very unlikely, because basiliximab blocks IL-2-R for only 30-45 days 19 and the patient was still on low-dose prednisolone and cyclosporine A at that time. No further bacterial or fungal infections occurred in our patients, probably because all patients had reconstituted before receiving basiliximab.…”
Section: Discussionmentioning
confidence: 83%
“…The rate of CMV-reactivation in our patients was within the expected range after allogeneic SCT. 18 A causal relation between fatal systemic inflammatory response syndrome and basiliximab in one of our patients more than 3 months after use of the antibody seems to be very unlikely, because basiliximab blocks IL-2-R for only 30-45 days 19 and the patient was still on low-dose prednisolone and cyclosporine A at that time. No further bacterial or fungal infections occurred in our patients, probably because all patients had reconstituted before receiving basiliximab.…”
Section: Discussionmentioning
confidence: 83%
“…The chimeric structure of basiliximab has both prolonged its half-life and reduced its immunogenicity. 13,14 Its convenient dosing regimen, just two 20-mg intravenous injections days 0 and 4, achieves blockade of the IL-2R for 4 to 6 weeks posttransplantation, precisely the period during which 80% to 90% of acute rejection episodes occur. Any more extensive blockade could increase the risk for excessive immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Early clinical studies 13,14 have shown that basiliximab is well tolerated, with no evidence of significant immunogenicity. These and other studies 15 also have shown that optimal administration of basiliximab is 20 mg intravenously the day of transplantation, followed by a second intravenous dose day 4 after transplantation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are two chimaeric monoclonal IL-2 receptor antagonists with different pharmacokinetic features: basiliximab, with a terminal half-life of 7 d, and daclizumab, with a terminal half-life of 20 d (Kovarik et al, 1997;Vincenti et (Henry & Rajab, 2002;Van Gelder et al, 2004;Webster et al, 2004). To the best of our knowledge, there has only been one prospective trial investigating the chimaeric IL-2 receptor antagonist daclizumab in steroid-refractory aGVHD (Przepiorka et al, 2000).…”
mentioning
confidence: 99%